PENGARUH PEMBELAJARAN BERDIFERENSIASI PRODUK DIPADU MODEL PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI UPT SMA NEGERI 1 WAJO - Irfan, Nadia Shazirah; Usman, Muhammad Arafah; Nasir, Muhammad; Rijal, Syamsu; Rompegading, Andi Badli (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Differentiated product learning provides students with opportunities to demonstrate their understanding through various forms of products, accommodating individual differences in interests, learning styles, and abilities. The implementation of the Project-Based Learning (PjBL) model was selected to enhance students’ active engagement in the learning process through real and relevant projects in biology. This study employed a quasi-experimental method using a posttest-only nonequivalent control group design. The results of data analysis revealed a positive and significant influence of differentiated product learning combined with the PjBL model on students’ learning outcomes. Students who participated in differentiated product learning integrated with the PjBL model achieved higher learning outcomes compared to those who experienced conventional learning. Therefore, it can be concluded that the application of differentiated product learning combined with the PjBL model is effective in improving the biology learning outcomes of Grade XI students.